From Mundane to Socially Significant Consumption: An Analysis of How Foodie Identity Work Spurs Market Formation. (March 2019) - Ulver, Sofia
How does dull turn into cool? Every now and then new markets emerge and consumption that used to be mundane and insignificant transforms into something socially significant. Using the theoretical lens of cultural system transformation, this research set out to analyze how consumers, through their identity work, unintentionally transform a market by negotiating its symbolic boundaries and expanding its borders in relation to their social surroundings. The results showed that consumer identity work contributes to forming the market by providing it with new symbolic meanings (epistemic, entertainment and erotic), by extending it with new discursive and material content (through epistemic refinement), and by expanding it through the provision (active and unintentional promotion of the consumption field to confirm their own identity) of new consumers. This research added to at least three ongoing conversations in marketing research; (i) to the macromarketing research stream on marketing systems by taking a cultural system perspective and recognizing the subtle but transformative impact of symbolic consumer meanings and identity work, (ii) to the consumer culture theory (CCT) research stream on market formation by highlighting consumers' unintentional change of a market through intense identity struggle in their immediate social circle, and (iii) to both above streams by highlighting what makes identity struggle distinct at a mundane rather than more controversial or extraordinary market.